Advanced Interventional Procedures for Knee Osteoarthritis: What Is the Current Evidence? - Dalili, Danoob; Holzwanger, Daniel J.; Fleming, Jacob W.; Igbinoba, Zenas; Dalili, Daniel E.; Beall, Douglas P.; Isaac, Amanda; Yoon, Edward S. (Seminars in Musculoskeletal Radiology, 2024)
The prevalence of knee osteoarthritis (OA) is the highest among all joints and likely to increase over the coming decades. Advances in the repertoire of diagnostic capabilities of imaging and an expansion in the availability and range of image-guided interventions has led to development of more advanced interventional procedures targeting pain related to OA pain while improving the function of patients presenting with this debilitating condition. We review the spectrum of established advanced interventional procedures for knee OA, describe the techniques used to perform these procedures safely, and discuss the clinical evidence supporting each of them.
Keywords: knee; osteoarthritis; pain; cryoneurolysis; ablation